THE DARK SIDE OF PERSONALIZATION: WHEN DATA-DRIVEN CUSTOMIZATION ERODES PERCEIVED AUTONOMY AND TRIGGERS REACTANCE - Neni Asmayati; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This article examines the dark side of data-driven personalization, focusing on how customization practices can erode perceived autonomy and trigger psychological reactance among consumers. While personalization enhances relevance, convenience, and engagement, it also raises concerns related to privacy, control, and perceived manipulation. Drawing on a narrative literature review, this study synthesizes insights from marketing and consumer psychology to explore the tension between personalization benefits and consumer discomfort. The findings highlight key themes, including the personalization–privacy paradox, perceived loss of control, and the role of trust and transparency. The study further explains the mechanism of reactance, where perceptions of manipulation lead to threats to freedom of choice, resulting in resistance, avoidance, and negative behavioral outcomes. In addition, several moderating factors are identified, such as the level of personalization, consumer data literacy, trust in brands, and cultural differences. A conceptual framework is proposed, linking personalization practices to perceived autonomy and privacy concerns, which in turn influence consumer responses. The article contributes by integrating psychological theory with marketing practice and offers managerial implications for designing ethical and user-centered personalization strategies. Future research should empirically validate the framework across contexts.